Data analytics for renewable energy integration : Second ECML PKDD Workshop, DARE 2014, Nancy, France, September 19, 2014, Revised Selected Papers - Aung, Zeyar; Madnick, Stuart; Woon, Wei Lee (Lecture Notes in Computer Science, 2014)
This book constitutes revised selected papers from the second ECML PKDD Workshop on Data Analytics for Renewable Energy Integration, DARE 2014, held in Nancy, France, in September 2014. The 11 papers presented in this volume were carefully reviewed and selected for inclusion in this book.